Continuidade e Metamorfose: A ruína em progressiva transformação - Tiago Jorge Vieira Saraiva (2020)
This dissertation aims to be a representation of the process resulting from a rehabilitation project in the small village of São Martinho das Chãs in Armamar. This process, although it's divided in three separate moments, it results from a constant relationship between them. Initially, we look to understand the pre-existence and the environment that surrounds it, with an objective analysis about the region and the metric survey carried out. This stage introduces new questions that should be addressed and analysed so it is possible to preserve the memory of the built environment. With this, we take some time to reflect about how we can intervene in built heritage. In addition to that we also look at some real examples of this kind of interventions. Taking everything in consideration, I developed a project that looks to adapt the built to the contemporary needs and to respond to all the conditionings imposed by a multiplicity of situations.